STRATEGIC BUDGETING FOR EDUCATION: CLASSIFICATION AND OPTIMAL UTILIZATION OF EDUCATIONAL FUNDING - Arsal, Fathur Riyadhi; Sidiq, Mohammad; Sayuti, Muhamad Deden Jalaludin (Managere: Indonesian Journal of Educational Management, 2024)
This study aims to explore and understand the concept of classification and utilization of education funds in Islamic educational institutions at the madrasah aliyah level. The concept is based on the concept of institutions that implement financing management by classifying and forming a priority scale of fund use. This study uses a qualitative approach with a descriptive method, with interview data collection techniques, observation, and documentation studies. The subject of the study was the madrasah aliyah treasurer. The results of the study indicate that the madrasah aliyah has been accredited A by BANSM in 2015 and has received a clean and targeted budget management predicate from the State Treasury Service Office. The budget can be classified into three types based on its benefits, namely as an assessment tool, a tool for authorizing expenditures, and an efficiency tool. The utilization of education funds is guided by activity components, cost units (including teacher salaries, facilities and infrastructure, and PBM support), procurement financing, and maintenance financing. The classification and utilization of education funds are aligned with the RKAM using the principle of priority scale, with funding sources including BOS funds and committee funds. This study contributes to understanding effective budget management in educational institutions, by emphasizing the importance of prioritized and transparent use of funds.